Institutional System Reform in the General Election Commission Through the Implementation of Digital-Based Applications - Abrar Kharas; Budi Setiyono; Yuwanto Yuwanto (Mahesa Research Center, 2023)
The advancement in science and technology, particularly in the information systems field, is proceeding rapidly. It is necessary to implement digitally-based applications to reform the institutional system to support the work and performance of the General Election Commission as the general election organizer. The qualitative research method explains and reveals how to reform the General Election Commission's institutional system by implementing digitally-based applications. Reference sources include books, scientific journals, laws and regulations, internet sources, and other relevant sources pertinent to this investigation. This study aims to discover, comprehend, and analyze information concerning institutional system reform at the General Election Commission via the implementation of digital-based applications. The research reveals that the General Election Commission is a state agency responsible for organizing general elections. Reform in an institution is necessary, a requirement of the times, due to the impact of technological advancements in all fields, systems, or orientation changes made to make things better than before. Changes made to the institutional system by the KPU have made it easier for the KPU to carry out its duties and responsibilities of providing the public with access to transparency, monitoring, and oversight at all stages of the election. Included are the Political Parties Information System (SIPOL), the KPU Member Information System and Ad Hoc Agency (SIAKBA), the Civil Service Information System (SIMPEG), as well as the Protect Your Rights Mobile Application and the Check Members of Political Parties Candidates for Election Contestants Through ID number.